Trimethylamine N-oxide promotes atherosclerosis via regulating the enriched abundant transcript 1/miR-370-3p/signal transducer and activator of transcription 3/flavin-containing monooxygenase-3 axis. Issue 1 (1st January 2022) - Liu, Aijun; Zhang, Yonglin; Xun, Shucan; Sun, Minli
ABSTRACT: Atherosclerosis (AS) is one of the main causes of cardiovascular diseases (CVDs). Trimethylamine N-oxide (TMAO) exacerbates the development of AS. This study aimed to investigate the roles of TMAO in AS. In this study, mice were fed with high fat food (HF) and/or injected with TMAO. Oil red O staining was applied for histological analysis. ELISA, qRT-PCR, and Western blot were conducted to determine the TMAO, serum, mRNA, and protein levels. CCK-8, colony formation assay, and flow cytometry assays were performed to detect the functions of human aortic endothelial cells (HUVECs). The results showed that TMAO induced thick internal and external walls and intimal plaques in vivo, and HUVEC dysfunction in vitro . TMAO and lncRNA enriched abundant transcript 1 (NEAT1) were increased in AS clinical samples and TMAO-HUVECs. Downregulated NEAT1 inhibited proliferation and promoted the apoptosis of HUVECs. NEAT1 regulated the expression of signal transducer and activator of transcription 3 (STAT3) via sponging miR-370-3p. Overexpression of miR-370-3p facilitated the effects of NEAT1 on the cellular functions of HUVECs, while STAT3 exerted opposing effects. The activation of STAT3 promoted the expression of flavin-containing monooxygenase-3 (FMO3). Taken together, our results show that TMAO-NEAT1/miR-370-3p/STAT3/FMO3 forms a positive feedback loop to exacerbate the development of AS. This novel feedback loop may be a promising therapeutic target for AS.